"Expressive Cool" and the Paradox of Black and White Males' Neighborhood Socialization Toward Education. Issue 3 (April 2018) - Johnson, Odis
This study explores how linkages between adolescents' educational attitudes and achievement vary according to race, expressive culture, and neighborhood collective socialization qualities. Specifically, the study examines (a) racial differences in how males' educational attitudes relate to their academic performance (i.e., "attitude–achievement paradox"); (b) how the attitude–achievement paradox varies according to Black and White males' expressive culture; and (c) the relation of collective socialization to racial differences in expressive cool, educational attitudes, and behavior. Using Maryland Adolescent Development in Context Study (MADICS) data, I find that an attitude–achievement paradox among African Americans disappears when neighborhood collective socialization is considered; that expressive cool seems to have a stronger connection to adolescents' achievement ideology rejection, and very little to their grade point average (GPA); and that neighborhood collective socialization decisively accounts for racial gaps in GPA. The concluding discussion considers why African Americans' adherence to achievement ideologies fails to shield their GPAs from neighborhood socialization risks to the extent it does so for White males.